Undergraduate Learning Outcomes for Achieving Data Acumen. Issue 2 (3rd May 2020) - Bargagliotti, Anna; Binder, Wendy; Blakesley, Lance; Eusufzai, Zaki; Fitzpatrick, Ben; Ford, Maire; Huchting, Karen; Larson, Suzanne; Miric, Natasha; Rovetti, Robert; Seal, Kala; Zachariah, Thomas
Abstract: It is imperative to foster data acumen in our university student population in order to respond to an increased attention to statistics in society and in the workforce, as well as to contribute to improved career preparation for students. This article discusses 13 learning outcomes that represent achievement of undergraduate data acumen for university level students across different disciplines.